Effect of antiepileptic drug (valproic acid) on children growth - Hussein Metwally Abdel Maksoud; Sherif Mahmoud El-Shazly; Mahmoud Helmy El Saied (SpringerOpen, 2016)
Background: Epilepsy often requires long-term antiepileptic drug therapy. Antiepileptic drugs are potentially an effective treatment for patients with epilepsy. Poor adherence is, however, very common in patients experiencing side-effects due to AEDs. The aim of this study: The aim of this study was to evaluate the effects of AED monotherapy by VPA on alterations in serum calcium levels and statural growth and body mass index in pediatric patients newly diagnosed with epilepsy. Patients and methods: The present study included 25 children, newly diagnosed with epilepsy and maintained on VPA monotherapy for at least one year. The serum levels of patients taking VPA were routinely monitored. Another 25 children with a history of simple febrile convulsions were included as a control group. All patients and controls were selected from Al-Azhar University hospital (new Damietta) during the period from June 2011 to June 2012. The main screening assessments included seizure frequency, vital signs, physical and neurologic examinations, medical history, and standard clinical laboratory tests (e.g., CBC, BUN, SGPT, SGOT); all these parameters were estimated at the start of the study, at 6 and 12 months. Weight and height measurements were recorded at the start of the study and at 6 and 12 months of continuous treatment of valproic acid. In addition serum calcium and glucose levels were obtained at the same time. Results: There was no significant difference between study and control groups at basal time regarding height, weight or BMI. On the other hand, there was a significant increase of weight and BMI and a decrease of height centiles at 6 months and 1 year; and as regards serum glucose, there was no significant difference between study and control group at basal time, while there was a significant increase in the study group in the control group at 6 months and 1 year. On the other hand, there was no significant difference between cases and controls as regards serum calcium at any time. Conclusion: Childhood and adolescence are crucial periods in which to attain peak bone mass, and it is a crucial period for growth in general; and most patients with epilepsy are diagnosed and treated in this period, therefore, AEDs, and especially VPA, should be used with caution in pediatric patients with epilepsy.